Measuring the patient experience in community mental health services for older people: A study of the Net Promoter Score using the Friends and Family Test in England. (24th September 2018) - Wilberforce, Mark; Poll, Sarah; Langham, Heather; Worden, Angela; Challis, David
Abstract : Objectives: The research aimed to explore the value of the Net Promoter Score as a service improvement tool and an outcome measure. The study objectives were to (1) explore associations between the Net Promoter Score with patient and service‐receipt characteristics; (2) evaluate the strength of association between the Net Promoter Score and a satisfaction score; and (3) evaluate its test‐retest reliability. Methods: A postal survey was sent to service users on caseloads of community mental health teams for older people in four localities of England. The survey collected the Net Promoter Score, a single satisfaction question, and data on socio‐demographics, clinical profile, and service receipt. Analysis used non‐parametric tests of association and exploratory least squares regression. A second survey was administered for test‐retest reliability analysis. Fieldwork concluded in April 2016. Results: For 352 respondents, the Net Promoter Score was negatively related to age and was lowest for those still within 6 months of their initial referral. Receiving support from a psychiatrist and/or support worker was linked to higher scores. A strong but imperfect correlation coefficient with the satisfaction score indicates they evaluate related but distinct constructs. It had a reasonable test‐retest reliability, with a weighted kappa of 0.706. Conclusions: Despite doubts over its validity in community mental health services, the Net Promoter Score may produce results of value to researchers, clinicians, service commissioners, and managers, if part of wider data collection. However, multi‐item measures would provide greater breadth and improved reliability.